The Analysis of Self-image in Yu Qian's Poetry - Yu, Fang; Numtong , Kanokporn; Petcharatip, Kewalee (Journal of Roi Kaensarn Academi, 2024)
The objectives of this research were 1) to analyze the depictions of self-image in the 623 poems contained in The Collected Works of Yu Qian. 2) to classify the types of self-image into meaningful dimensions or aspects. The sample are 623 poems written by Yu Qian. They were selected by a comprehensive examination of all poems authored by Yu Qian within the aforementioned book. The research instrument for the data collection was a thematic analysis framework specifically designed for interpreting the 623 poems and analyzing the portrayal of the poet's self-image within them. The statistics for data analysis involved qualitative techniques such as literature research, descriptive analysis, and thematic analysis. The research results were found as follows: The study identifies four types of self-image — external, spiritual, social, and family. 2) The external image encompasses various personas such as a brave general, a homesick traveler, a leisurely literati, and a lonely or elderly poet. 3) The spiritual image emphasizes Yu Qian’s noble character, unwavering integrity, nostalgic emotions, optimism, open-mindedness, lofty ambitions, vigor and unrestrainedness. 4) The social image highlights his reputation as an upright and incorruptible official, as well as someone who possessed deep affection and sincerity. 5) The family image portrays Yu Qian as a filial son, a devoted husband, and an affectionate father. By examining Yu Qian’s self-image through his poetry, this analysis contributes to a better understanding of both his literary works and the history of the Ming Dynasty. It is recommended that future investigations delve into Yu Qian and his poetry, exploring themes such as his experiences with different seasons, encounters with natural elements, and interactions with various emperors during his lifetime.